Ethnobotany - Gabriel Tonga, Noweg; Samuel, Lihan; Julia, Nelson; Sabella, Justin (UNIMAS Publisher, 2024)
Sarawak is renowned for its vast forests and diverse natural resources, S and its indigenous peoples have intimate association with the natural environment. The forest environment, in particular, has beenthe primary source of their sustenance before sedentary farming was adopted in these tribal communities. They harvest ethnobotanical resources for food, medicine, lumber wood and fibre (c.g. bamboo and rattan) for making houschold indoor furnishings, farming utensils and crafts.